KELIMPAHAN JENIS SATWA LIAR DI TANJUNG BINEREAN KECAMATAN PINOLOSIAN TENGAH KABUPATEN BOLAANG MONGONDOW SELATAN - Nicodemus Malir; Marthen T. Lasut; Johny S. Tasirin (COCOS, 2017)
Binerean cape retains a high biodiversity, including the diversity of wildlife species. This research aims to know the abundance of wildlife species using camera traps in South Bolaang Mongondow Regency. The data was taken using Bushnell trophy-cam and Reconyx camera traps. The results show that there are 15 species from 13 families of wildlife in Binerean Cape. The most abundant wildlife species is the macaques (Macaca nigra) at 65.3% with an encouter rate of 4.61 photos/days. It is followed by Sulawesi wild boar (Sus celebensis) with 13.5% abundance or 0.96 photos/day camera trapping. Third abundance is Sulawesi rats (Paroromys sp.) at 13.2% abundance and 0.93 photos/day. The lowest abundance at 0,1%Â  or less are common emerald doves (Chalcophaps indica), red-bellied pitta (Pitta erythrogaster), whitish dwarf squirre (Prosciurillus leucomus), common water monitors (Varanus salvator), dan red-backed thrush (Zoothera erythronota). Keyword: Headland Binerean, Animals Wild, Species diversity